Catalytic Synergies in Bimetallic RuPt Single–Atom Catalysts via Speciation Control. (14th September 2022) - Giulimondi, Vera; Ruiz–Ferrando, Andrea; Clark, Adam H.; Kaiser, Selina K.; Krumeich, Frank; Martín, Antonio J.; López, Núria; Pérez–Ramírez, Javier
Abstract: Bimetallic single–atom catalysts (b–SACs) have recently gained prominence by virtue of the unique catalytic cooperative interactions they can exhibit, intertwining electronic and geometric effects. To date, research efforts have exclusively focused on direct mechanisms such as electron density transfer or sequential reactivity. Herein, the first study on indirect, coordination–induced catalytic synergies in carbon‐supported RuPt SACs is conducted. To this end, a holistic approach is developed, combining i) precision synthesis, ii) advanced characterization, iii) exploration of single–site adsorption properties via the hydrogen evolution reaction, and iv) modeling through density functional theory. Despite the lack of both intermetallic coordination in the first or second shell and charge redistribution effects, the RuPt SACs exhibit a H2 formation rate enhanced up to 15–fold compared with their monometallic counterparts. To unfold the origin of the intermetallic cooperativity, modifications of the structural and catalytic properties induced by the integration of a second metal species are investigated. Thus, Pt atoms are found to selectively occupy the most energeticallyfavorable cavities in the support, prompting Ru atoms to assume a distinct, more active, configuration. This contribution unveils a novel principle of bimetallic cooperativity, demonstrating the key role of integrative experimental and computational analyses in studying b–SACs. Abstract : Coordination–induced cooperativity effects between isolated Ru and Pt atoms are investigated via the hydrogen evolution reaction, selected as a probe for single–site H–adsorption properties. Pt atoms are found to selectively occupy the most energetically favorable cavities in the carbon host, prompting Ru atoms to adopt a distinct and more active configuration.